Vestibular dysfunction in lateral semicircular canal dysplasia - Yun, Ji Min; Kim, Sung Huhn; Bae, Seong Hoon (Frontiers in Neurology, 2024)
Lateral semicircular canal (LSCC) dysplasia is the most common inner ear malformation. The severity of dysplasia can appear in various spectrums, from a short and broad LSCC with normal or small-sized central bony island (CBI) to a single fluid-filled cavity confluent with the vestibule without CBI. However, reports on the association between LSCC dysplasia and the loss of vestibular function are still lacking. In this study, the results of vestibular function tests (caloric test and video-head impulse test (vHIT)) in patients with LSCC dysplasia were analyzed and compared between groups with and without CBI.This study retrospectively enrolled 17 patients (23 ears) who had LSCC dysplasia following computed tomography or magnetic resonance imaging and underwent vestibular function tests. LSCC dysplasia was observed unilaterally in 11 patients and bilaterally in six patients. Nine of 23 ears had CBIs, and 14 ears had no CBI. Three of 17 patients experienced dizziness.Abnormal caloric tests were detected in 11 of the 16 patients who underwent the caloric tests (69%); in contrast, 11 of 12 patients who underwent the vHIT (92%) had normal LSCC vestibulo-ocular reflex (VOR) gain on vHIT. A significant correlation was found between the maximum slow-phase velocity of the caloric test and LSCC VOR gain of the vHIT (correlation coefficient 0.792, p = 0.004). The CBI-absent group showed significantly lower SPV and LSCC VOR gains than the CBI-present group (p = 0.001 and 0.004, respectively).LSCC dysplasia impairs VOR function, especially in the absence of CBI.